The Effect of Lecture-Based and Interactive Tauhid Learning Models on Students' Cognitive Learning Outcomes in Islamic Elementary Education - Hijratul Hasri; Muhammad Musfiatul Wardi; Mappanyompa Mappanyompa; Noel Jimbai Balang (Bidayatuna, 2026)
Strengthening the understanding of Tawhid in elementary schools is important because its abstract concepts require effective learning strategies. With the dominance of lecture methods that minimize student involvement, an interactive approach is needed to encourage active participation and cognitive deepening. This study examines the individual and combined effects of lecture-based Tawhid instruction (X1) and interactive Tawhid instruction (X2) on students’ cognitive learning outcomes (Y) among 58 fifth-grade students at an Integrated Islamic Elementary School selected via census sampling. This study employs an explanatory quantitative design. The independent variables were operationalized using a 15-item structured questionnaire on a Likert scale that measured the quality of implementation of each learning model as experienced by the students, with construct validity confirmed through corrected item-total correlations (r ≥ 0.30) and Cronbach’s Alpha coefficients (α = 0.84 for X1; α = 0.81 for X2; α = 0.87 for Y). Cognitive learning outcomes were measured through documentation of daily cognitive test scores obtained directly from subject teachers, including pre- and post-implementation scores. Data were analyzed using paired-sample t-tests and multiple linear regression at α = 0.05. The results of the paired-sample t-test indicated a statistically significant increase in cognitive scores (t = −5.406; df = 57; p < 0.001). Both models simultaneously explained 16.1% of the variation in cognitive learning outcomes (F = 5.261; p = 0.008; R² = 0.161). The interactive model showed a significant positive effect (β = 0.343; p = 0.022), while the lecture model did not reach significance (β = −0.303; p = 0.071). The findings advance a theoretical implication that interactive pedagogical strategies mediate the translation of abstract Tawhid concepts into measurable cognitive achievement, highlighting the necessity of active engagement frameworks in Islamic elementary learning. This conceptualization contributes a refined understanding of instructional effectiveness, offering guidance for future curriculum design that integrates traditional and interactive learning paradigms.